Exploring The Potential Of Transforming Murut Tribal Art Lansaran Into Contemporary Art Form - Sarah Naemah, Aman Leong (Universiti Malaysia Sarawak, (UNIMAS), 2016)
The core idea of this research was the researcher's respond towards Western colonials' theory that differentiates between high art and low art. Researcher's main objective was to explore the potential of Lansaran, a Murut cultural object to be translated and transformed into a contemporary art form. Researcher had used observation and research through scholarly journals and books to conduct this study. The findings of the research were then expressed into an artwork. The artwork was done to expose the audiences on the importance of knowing one's own culture. In a nutshell, this research has opened a new perspective to the researcher as well as the audiences on cultural object and contemporary art. The final result of this research possesses high potential for expansion, alongside with the fast developing art world.